2015
DOI: 10.1108/bepam-03-2014-0017
|View full text |Cite
|
Sign up to set email alerts
|

BIM in the operations stage: bottlenecks and implications for owners

Abstract: Purpose – The use of Building Information Modelling (BIM) in the Netherlands is increasing. Studies show that BIM is mainly used in the lifecycle stages of initiation, development and realisation. Owners and operators are presumably yet to discover the added value of BIM for maintenance and information management within their organisations. The purpose of this paper is to investigate information management during the operations stage from the viewpoint of owners and determines the added value o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 16 publications
0
60
0
2
Order By: Relevance
“…The research disqualifies the pure quantitative approach due to the lack of established knowledge on BIM in FM and value of facilities information (Bosch et al, 2015). Therefore, priority was given to adopt the interpretative approach to mine the data in detail.…”
Section: Methodsmentioning
confidence: 99%
“…The research disqualifies the pure quantitative approach due to the lack of established knowledge on BIM in FM and value of facilities information (Bosch et al, 2015). Therefore, priority was given to adopt the interpretative approach to mine the data in detail.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, there has been growing interest in extending the use of BIM to the operation stage, usually for the benefit of institutional clients who remain involved in the use of their buildings in a technical or financial sense (Bosch, Volker, & Koutamanis, 2015;Love, Matthews, Simpson, Hill, & Olatunji, 2014). BIM helps to perform additional tasks of registering.…”
Section: B U I L D I N G I N F O R M a T I O N Mo D E L I N G (B I M )mentioning
confidence: 99%
“…It could be argued that the number of stakeholders can be reduced through delegation: local authorities can be assumed to represent the interests of citizens, demolition firms could be seen as the front end of a C&DW processing chain that incorporates waste processing enterprises etc. However, the relation between authorities and citizens is significant in terms of throughout the lifecycle of a building, with significant benefits to owners and operators [30]. In urban mining studies, BIM has already been identified as an appropriate framework for information management.…”
Section: Information Processing Designmentioning
confidence: 99%